BMS-284756 in Experimental Cephalosporin-Resistant Pneumococcal Meningitis - Rodriguez-Cerrato, Violeta (American Society for Microbiology, 2001)
BMS-284756 is a novel des-fluoro(6) quinolone with a broad antimicrobial activity, including Streptococcus pneumoniae. The purpose of this study was to evaluate the pharmacodynamic profile and effectiveness of BMS-284756 for therapy of experimental meningitis caused by penicillin- and cephalosporin-resistant S. pneumoniae (CRSP). Meningitis was induced in rabbits by intracisternal inoculation of CRSP. BMS-284756 was given intravenously 16 h after intracisternal inoculation in single doses of 2.5 (n = 5 animals), 5 (n = 6), 10 (n = 6), 20 (n = 8), and 30 mg/kg (n = 6), in two doses of 10 mg/kg each separated by 5 h (n = 4), and as a 20-mg/kg dose followed 5 h later by 10 mg/kg (n = 5). The MICs and MBCs of BMS-284756, ceftriaxone, and vancomycin were 0.06 and 0.06, 4 and 4, and 0.25 and 0.25 μg/ml, respectively. After single doses of 10, 20, and 30 mg/kg, the maximum concentrations in cerebrospinal fluid (CSF) (mean ± standard deviation) were 0.32 ± 0.12, 0.81 ± 0.38, and 1.08 ± 0.43 μg/ml, respectively; the elimination half-life in CSF was 4.5 to 6.3 h. The CSF bacterial killing rates (BKR) at 5 h of the single-dose regimens of 10, 20 and 30 mg/kg were −0.84 ± 0.48, −1.09 ± 0.32, and −1.35 ± 0.05 Δlog(10) CFU/ml/h. The BKR(0–5) of the divided regimens (10 mg/kg twice and 20 mg/kg followed by 10 mg/kg) was −0.82 ± 0.52 and −1.24 ± 0.34 Δlog(10) CFU/ml/h, respectively. The BKR(0–5) of the combined therapy with vancomycin and ceftriaxone was −1.09 ± 0.39 Δlog(10) CFU/ml/h. The penetration of BMS-284756 into purulent CSF relative to plasma was 14 to 25%. The bactericidal effect of BMS-284756 in CSF was concentration dependent. BMS-284756 at 30 mg/kg as a single or divided dose was as effective as standard therapy with vancomycin and ceftriaxone.